Manejo de residuos sólidos municipales en la localidad de Naranjos, provincia de Rioja - Palma Vergara, Liliana Isabel (2012)
The present thesis project titled Management of Municipal Solid Waste of the locality of Naranjos town, Rioja province - San Martín, has to see basically with the whole system of Evaluation and managing of the Solid Waste of municipal origin that one comes generating in the locality of Naranjos town, with the principal aim to be one of the healthy municipalities of the Rioja province, beside contributing in the process of environmental municipal management that must be implementad in an obligatory way as to indicate to him the Law of the National System of Environmental Management N ° 28245. The generation and characterization of municipal solid waste, are very important parameters for the decision making in regard to projection and design of the systems of management and final disposal of solid waste, you should always pay special attention to this parameter from the selection of the sample until its statistical analysis. Within this work analyzes the domestic municipal solid waste (solid residues generated in houses or rooms ), using the method of analysis of Sol id Residues recommended by the C.E.P.I.S and the Manual of the Dr. Carlos Caycho Chumpitaz, which have been in use in the different districts of Metropolitan Lima for determining the quantity and characteristics of the solid domiciliary residues from a Random Stratified Sampling The objective of this study is to generate qualitative and quantitative information, using statistical sampling methods and analyzes indicated, for the determination of the capita generation. Capita, volumetric weight and the percentage of products recoverable and non-recoverable, with the purpose of documenting the findings and adjustments necessary for the establishment of alternative solutions on the waste management and disposal of the Pardo Miguel district. Key words: Solid Waste, Environmental Management.